2018
DOI: 10.3390/rs10081226
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover Change in the Lower Yenisei River Using Dense Stacking of Landsat Imagery in Google Earth Engine

Abstract: Climate warming is occurring at an unprecedented rate in the Arctic due to regional amplification, potentially accelerating land cover change. Measuring and monitoring land cover change utilizing optical remote sensing in the Arctic has been challenging due to persistent cloud and snow cover issues and the spectrally similar land cover types. Google Earth Engine (GEE) represents a powerful tool to efficiently investigate these changes using a large repository of available optical imagery. This work examines la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 56 publications
(72 reference statements)
1
35
0
Order By: Relevance
“…Landsat TOA reflectance-based EVI values were generally higher than surface reflectance (SR) based values [78] and therefore TOA data showed greater potential to provide accurate phenology-based classification [53,79,84,85]. Several studies have successfully applied TOA data for mapping the paddy rice [63,78,79,86,87] and mapping the vegetation distribution [17,22,53,84,88] using phenology-based methods. These studies have suggested that TOA data can be used for mapping with higher accuracy.…”
Section: Collection Of Landsat Data and Image Compositementioning
confidence: 99%
See 3 more Smart Citations
“…Landsat TOA reflectance-based EVI values were generally higher than surface reflectance (SR) based values [78] and therefore TOA data showed greater potential to provide accurate phenology-based classification [53,79,84,85]. Several studies have successfully applied TOA data for mapping the paddy rice [63,78,79,86,87] and mapping the vegetation distribution [17,22,53,84,88] using phenology-based methods. These studies have suggested that TOA data can be used for mapping with higher accuracy.…”
Section: Collection Of Landsat Data and Image Compositementioning
confidence: 99%
“…In recent years, GEE has been widely used for global-scale applications such as characterizing global forest cover change; forest expansion, loss, and gain from 2000 using large collections of Landsat scenes [5]; and crop yield estimation [21,22]. Other studies have also confirmed the ease of integrating various sources of temporal satellite imagery data and automating image classification routines for vegetation and land cover mapping using the GEE [17,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Inglada et al, provided the land cover of France using Sentinel-2 products for 17 land cover classes [7]. Also, a cloud-based platform and dense stack satellite time series were utilized to provide artic land cover [8]. Belgiu et al, investigated the ability of a Machine Learning (ML) methodology in land cover mapping in different agro-ecological regions of the planet [9].…”
Section: Introductionmentioning
confidence: 99%